Identification of the genetic basis of sow pelvic organ prolapse - Bhatia, Vishesh; Stevens, Tomas; Derks, Martijn F. L.; Dunkelberger, Jenelle; Knol, Egbert F.; Ross, Jason W.; Dekkers, Jack C. M. (Frontiers in Genetics, 2023)
Pelvic organ prolapse (POP) is one contributor to recent increases in sow mortality that have been observed in some populations and environments, leading to financial losses and welfare concerns. With inconsistent previous reports, the objective here was to investigate the role of genetics on susceptibility to POP, using data on 29,526 genotyped purebred sows (25K), collected from 2012 to 2022 in two US multiplier farms with high incidence. The incidence rate of POP was 7.1% among culled and dead sows and ranged from 2 to 4% of all sows present by parity. Given the low incidence of POP for parities 1 and >6, only data from parities 2 to 6 were retained for analyses. Genetic analyses were conducted both across parities, using cull data (culled for POP versus another reason), and by parity, using farrowing data (culled for POP versus culled for another reason or not culled). Estimates of heritability from univariate logit models on the underlying scale were 0.35 ± 0.02 for the across parity analyses and ranged from 0.41 ± 0.03 in parity 2 to 0.15 ± 0.07 in parity 6 for the by-parity analyses. Estimates of genetic correlations of POP between parities based on bivariate linear models indicated a similar genetic basis of POP across parities but decreased with increasing distance between parities. Genome wide association analyses revealed six 1 Mb windows that explained more than 1% of the genetic variance in the across parity data. Most regions were confirmed in several by-parity analyses. Functional analyses of the identified genomic regions showed a potential role of several genes on chromosomes 1, 3, 7, 10, 12, and 14 in susceptibility to POP, including the Estrogen Receptor gene. Gene set enrichment analyses showed that genomic regions that explained more variation for POP were enriched for several terms from custom transcriptome and gene ontology libraries. In conclusion, this study confirms the influence of genetics in the susceptibility of POP in this population and environment and identified candidate genes and biological processes to target to better understand and mitigate the incidence of POP.